Biomagnetic and bioelectric detection of gastric slow wave activity in normal human subjects-a correlation study - Somarajan, S; Muszynski, N D; Obioha, C; Richards, W O; Bradshaw, L A (Physiological measurement, 2012)
We measured gastric slow wave activity simultaneously with a Superconducting Quantum Interference Device (SQUID) magnetometer, mucosal electrodes and cutaneous electrodes in 18 normal human subjects (11 women and 7 men). We processed signals with Fourier spectral analysis and SOBI blind-source separation techniques. We observed a high waveform correlation between the mucosal electromyogram (EMG) and multichannel SQUID magnetogastrogram (MGG). There was a lower waveform correlation between the mucosal EMG and cutaneous electrogastrogram (EGG), but the correlation improved with the application of SOBI. There was also a high correlation between the frequency of the electrical activity recorded in the MGG and in mucosal electrodes (r = 0.97). We concluded that SQUID magnetometers noninvasively record gastric slow wave activity that is highly correlated with the activity recorded by invasive mucosal electrodes.